Can f(R) gravity isotropise a pre-bounce contracting universe?. Issue 9 (1st September 2022) - Arora, Simran; Mandal, Sanjay; Chakraborty, Saikat; Leon, Genly; Sahoo, P.K.
Abstract: We address the important issue of isotropisation of a pre-bounce contracting phase in f ( R ) gravity, which would be relevant to constructing any viable nonsingular bouncing scenario in f ( R ) gravity. The main motivation behind this work is to investigate whether the f ( R ) gravity, by itself, can isotropise a contracting universe starting initially with small anisotropy without incorporating a super-stiff or non-ideal fluid, impossible in general relativity. Considering Bianchi I cosmology and employing a dynamical system analysis, we see that this is not possible for R n ( n > 1) and R + αR 2 ( α > 0) theory, but possible for 1/ α e αR ( α > 0) theory. On the other hand, if one does not specify an f(R) theory a priori but demands a cosmology smoothly connecting an ekpyrotic contraction phase to a nonsingular bounce, the ekpyrotic phase may not fulfil the condition for isotropisation and physically viability simultaneously.